2018
DOI: 10.3390/mi9090460
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Enhancement Using Bimetal Surface Plasmon-Coupled Emission from 5-Carboxyfluorescein (FAM)

Abstract: We demonstrate the enhancement of fluorescence emission from a dye, 5-carboxyfluorescein (FAM), which couples with surface plasmons at the spectral channels of excitation and emission. Experiments and calculations revealed that bimetallic (gold-silver) plasmon, as compared to the monometallic ones, allowed such coupling to be enhanced, at both the spectral channels. We achieved the maximum fluorescence enhancement level of 46.5-fold, with markedly high reproducibility (coefficient of variation ~ 0.5%) at a FAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 38 publications
(52 reference statements)
0
16
0
Order By: Relevance
“…In estimating the optical power of pure fluorescence, which must be used for fluorescence enhancement analysis, dark noise power included in the detected fluorescence power needs to be subtracted. 60,61 Fig. 8 shows the fluorescence optical power measured via the optical systems described in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In estimating the optical power of pure fluorescence, which must be used for fluorescence enhancement analysis, dark noise power included in the detected fluorescence power needs to be subtracted. 60,61 Fig. 8 shows the fluorescence optical power measured via the optical systems described in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, in the case of FAM/SH-DNA 3 W J, a substantially increased LSPR band was observed compared to that with SH-DNA 3 W J. Presumably, the results showed that the fluorescent dye molecule in the DNA could couple with the surface plasmon that confers a high refractive index onto the DNA 3 W J-modified hAuSN substrate [21]. Based on the combined result, the prepared nanobio heterolayer can be used to effectively detect HA protein.…”
Section: Plasmon Effect Characterization Of Ha Protein/ Dna 3wj On Hausnmentioning
confidence: 85%
“…The electron oscillation originating from electromagnetic waves triggers a binding interaction event in the nanoparticle interface, thus providing high sensitivity [19]. Moreover, this plasmonic event can be tuned to excite the fluorescence dye-labeled bioprobe that exhibits ultra-sensitivity in order to detect the H5N1 virus [20,21]. Advanced bioprobes have been developed to detect H5N1 accurately with high sensitivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…150 It is the first reusable SPCE device for an ultrafast and sensitive DNA detection in whole blood. The great compatibility of the DNA component allows for a further extension of the DNA architecture with silver nanoparticles, 151 carbon dots, 152 or a bimetallic substrate 153,154 in SPCE measurements.…”
Section: A Silicon-basedmentioning
confidence: 99%